Identification of early ammonium nitrate-responsive genes in rice roots. Issue 1 (December 2017) - Yang, Hsiu-Chun; Kan, Chia-Cheng; Hung, Tzu-Huan; Hsieh, Ping-Han; Wang, Shi-Yun; Hsieh, Wei-Yu; Hsieh, Ming-Hsiun
Abstract Ammonium has long been used as the predominant form of nitrogen source for paddy rice (Oryza sativa ). Recently, increasing evidence suggests that nitrate also plays an important role for nitrogen acquisition in the rhizosphere of waterlogged paddy rice. Ammonium and nitrate have a synergistic effect on promoting rice growth. However, the molecular responses induced by simultaneous treatment with ammonium and nitrate have been less studied in rice. Here, we performed transcriptome analysis to identify genes that are rapidly regulated by ammonium nitrate (1.43 mM, 30 min) in rice roots. The combination of ammonium and nitrate preferentially induced the expression of nitrate-responsive genes. Gene ontology enrichment analysis revealed that the early ammonium nitrate-responsive genes were enriched in "regulation of transcription, DNA-dependent" and "protein amino acid phosphorylation" indicating that some of the genes identified in this study may play an important role in nitrogen sensing and signaling. Several defense/stress-responsive genes, including some encoding transcription factors and mitogen-activated protein kinase kinase kinases, were also rapidly induced by ammonium nitrate. These results suggest that nitrogen metabolism, signaling, and defense/stress responses are interconnected. Some of the genes identified here may be involved in the interaction of nitrogen signaling and defense/stress-response pathways in plants.